Hukum Adat sebagai Alternatif Penyelesaian Sengketa di Ruang Virtual pada Masyarakat Kepulauan Kei - Alexander Frenzo Narahawarin; Andreas M.D Ratuanak; Jurgen R. Litualy (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
This study aims to examine the role of Larvul Ngabal customary law as an alternative to resolving disputes that occur in virtual space in the Kei Islands community. This study uses a socio-legal research method with a qualitative approach. Data were collected through observation and in-depth interviews with traditional leaders and the community in the Kei Islands. The results of the study indicate that Larvul Ngabal customary law has significant potential in resolving disputes in virtual space, especially because it emphasizes the principles of deliberation, consensus, and restoration of social relations. The Kei Islands community tends to choose customary law because it is considered cheaper, fairer, faster, and able to provide comprehensive recovery compared to state law.